A pathway-based approach investigating the genes encoding interleukin-1β, interleukin-6 and the interleukin-1 receptor antagonist provides new insight into the genetic susceptibility of Achilles tendinopathy. Issue 13 (10th May 2011) - September, Alison V; Nell, Erica-Mari; O'Connell, Kevin; Cook, Jill; Handley, Christopher J; van der Merwe, Lize; Schwellnus, Martin; Collins, Malcolm
Abstract : Objectives: Achilles tendinopathy (AT) is a multifactorial condition for which genetic risk factors have been identified. A pathway-based approach was used to investigate genes within the inflammatory pathway. Methods: Functional polymorphisms within IL-1β (−31T→C and −511C→T), IL-1RN (variable number tandem repeat) and IL-6 (−172G→C) were investigated for associations with AT in a South African (SA) and Australian (AUS) case–control studies. A total of 369 (161 SA and 208 AUS) asymptomatic control participants (CON) and 175 (90 SA and 85 AUS) participants with AT (TEN) were genotyped. Allele combinations were constructed using the above polymorphisms in combination with the COL5A1 Bst UI RFLP. Results: Independently, no associations were observed between any of the polymorphisms tested and risk of TEN. The allele combinations of five polymorphisms were, however, found to have a highly significant relationship with AT (p=0.005), after adjusting for gender and country (SA or AUS). Conclusions: Variations within the interleukin genes and the COL5A1 Bst UI CC genotype are collectively significantly associated with risk of AT. This research emphasises that a pathway-based genetic association study may be a more effective approach to capture and understand the genetic risk factors underlying the multifactorial conditions, such as AT.